Age and growth of olivancillaria deshayesiana (gastropoda: Olividae) in the southwestern Atlantic Ocean - Arrighetti, Florencia (2012)
The population structure, particularly growth, age, mortality and somatic production of the olivid snail Olivancillaria deshayesiana were investigated. Annual formation of internal shell growth marks was confirmed by the record of stable oxygen isotopes in the shell, which reflects seasonal patterns of water temperature. A von Bertalanffy growth model fitted to 81 size-atage data pairs, indicating that O. deshayesiana may attain 31 mm SL in about 10 years. The estimated total mortality Z and natural mortality M were 0.651 y-1 and 0.361 y -1, respectively. Fishing mortality F was 0.290 y -1, and the exploitation rate E was 0.445, indicating that this population was not overexploited at the time of the study. However, this situation may well change in the future, since the important prawn and shrimp fisheries (in intensity and scale) in the Mar del Plata area (38°20'S, 57°37'W) may indirectly affect the exploitation status of the studied population.